ANALISIS PENGARUH KINERJA KEUANGAN DAN PENGUNGKAPAN LINGKUNGAN TERHADAP NILAI PERUSAHAAN - Fahmi Mumtazah; Agus Purwanto (Diponegoro Journal of Accounting, 2020)
This study aims to empirically examine the relation between financial performance, environmental disclosure and firm value. The independent variables in this study are NPL, LDR, GCG, ROA, CAR and environmental disclosure. The dependent variable used in this research is Tobin’s Q. This study uses secondary data from financial statements of bank companies listed on Indonesia Stock Exchange in 2013-2017. The sampling method used is purposive sampling and the number of sample is 75 banks. This research using multiple regression analysis.The result of this study shows that GCG and ROA has positive effect on Tobin’s Q, LDR has negative effect on Tobin’Q, NPL, CAR and environmental disclosure has no significant effect on Tobin’s Q.